Oral Glutamine May Have No Clinical Benefits to Prevent Radiation-Induced Oral Mucositis in Adult Patients With Head and Neck Cancer: A Meta-Analysis of Randomized Controlled Trials - Shuai, Ting; Tian, Xu; Xu, Ling-Li; Chen, Wei-Qing; Pi, Yuan-Ping; Zhang, Lin; Wan, Qiao-Qin; Li, Xiu-E (Frontiers in Nutrition, 2020)
Objectives: The role of oral glutamine for the management of oral mucositis (OM) has not yet been confirmed. The objective of the present study is to further investigate whether oral glutamine is effective in preventing and treating OM among patients with head and neck cancer (HNC) receiving radiotherapy alone or concurrent with chemotherapy. Methods: A systematic search was performed in PubMed, EMBASE, EBSCO, and Cochrane Central Register of Controlled Trials (CENTRAL) to capture all potential citations from the inception to June 2019. Then data extraction and assessment of risk of bias were carried out after selecting the eligible citations. RevMan 5.3 software was used to perform all statistical analyses. Results: Six randomized controlled trials (RCTs) including 441 patients were included in the final analysis. The meta-analysis showed that oral glutamine couldn’t significantly decrease the incidence of OM (risk ratio [RR] = 0.98, 95% confidence interval [CI] = 0.94 - 1.02) and alleviate the development of moderate or severe grade of OM (Moderate-to-severe OM: RR = 0.81, 95% CI = 0.59 - 1.12; Severe OM: RR = 0.45, 95% CI = 0.13 - 1.52). But oral glutamine may have the potential to reduce the opioid use (RR = 0.84, 95% CI = 0.71 - 0.99). The role of oral glutamine in delaying the onset of OM remains uncertain due to conflicting results between quantitative (mean difference [MD] = 4.11 days, 95% CI = 3.49 - 4.73) and qualitative results. Conclusions: Oral glutamine may have no clinical benefits to prevent or reduce the incidence and severity of radiation-induced OM in patients with HNC receiving radiotherapy alone or concurrent with chemotherapy. It is also uncertain whether oral glutamine can delay the onset of OM. But it may have the potential to relieve the degree of oral pain. Nevertheless, we must cautiously interpret the results because the observed effect size for delay in mucositis start or reduction in opioid use is marginal. Moreover, further RCTs with more rigorous methodology and large-scale are required to enhance the quality of evidence.